Genetic Inactivation of ZCCHC6 Suppresses Interleukin‐6 Expression and Reduces the Severity of Experimental Osteoarthritis in Mice. Issue 4 (6th March 2019) - Ansari, Mohammad Y.; Khan, Nazir M.; Ahmad, Nashrah; Green, Jonathan; Novak, Kimberly; Haqqi, Tariq M.
Abstract : Objective: Cytokine expression is tightly regulated posttranscriptionally, but high levels of interleukin‐6 (IL‐6) in patients with osteoarthritis (OA) indicate that regulatory mechanisms are disrupted in this disorder. The enzyme ZCCHC6 (zinc‐finger CCHC domain–containing protein 6; TUT‐7) has been implicated in posttranscriptional regulation of inflammatory cytokine expression, but its role in OA pathogenesis is unknown. The present study was undertaken to investigate whether ZCCHC6 directs the expression of IL‐6 and influences OA pathogenesis in vivo. Methods: Human and mouse chondrocytes were stimulated with recombinant IL‐1β. Expression of ZCCHC6 in human chondrocytes was knocked down using small interfering RNAs. IL‐6 transcript stability was determined by actinomycin D chase, and 3′‐uridylation of microRNAs was determined by deep sequencing. Zcchc6 −/− mice were produced by gene targeting. OA was surgically induced in the knee joints of mice, and disease severity was scored using a semiquantitative grading system. Results: ZCCHC6 was markedly up‐regulated in damaged cartilage from human OA patients and from wild‐type mice with surgically induced OA. Overexpression of ZCCHC6 induced the expression of IL‐6, and its knockdown reduced IL‐6 transcript stability and IL‐1β–induced IL‐6 expression in chondrocytes. Reintroduction of Zcchc6 in Zcchc6 −/− mouse chondrocytes rescued the IL‐1β–induced IL‐6 expression. Knockdown of ZCCHC6 reduced the population of micro‐RNA 26b (miR‐26b) with 3′‐uridylation by 60%. Zcchc6 −/− mice with surgically induced OA produced low levels of IL‐6 and exhibited reduced cartilage damage and synovitis in the joints. Conclusion: These findings indicate that ZCCHC6 enhances IL‐6 expression in chondrocytes through transcript stabilization and by uridylating miR‐26b, which abrogates repression of IL‐6. Inhibition of IL‐6 expression and significantly reduced OA severity in Zcchc6 −/− mice identify ZCCHC6 as a novel therapeutic target to inhibit disease pathogenesis.